2020
DOI: 10.21300/21.4.2020.7
|View full text |Cite
|
Sign up to set email alerts
|

The Unexpected Benefits of Customer Discovery for Research, Teaching, Economic Development, and Innovation

Abstract: The Innovation-Corps™ (I-Corps) program was created by the National Science Foundation (NSF) in 2011 to help translate NSF-funded academic research to market. Working with coordi- nating partner VentureWell, the NSF offers select participants from U. S. academic laboratories the opportunity to immerse themselves in a process to test and explore the opportunities and value of their ideas in the marketplace. Participants talk to potential customers, partners, and competitors to refine their research ideas into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The interviewees clarify that they need to master the complexity and create an understanding of the technology among the employees before the implementation of ODT into the strategy and the alignment of the business models can occur (Mukherjee, 2018;Tronvoll et al, 2020;Wu et al, 2021b). This approach contrasts with previous studies, which have called for strategy alignment followed by the search for and implementation of appropriate technologies (Bosman et al, 2020;Sinha and Fukey, 2021). SME employees have indicated that there is a knowledge gap regarding the handling of the collected data.…”
Section: Discussionmentioning
confidence: 97%
“…The interviewees clarify that they need to master the complexity and create an understanding of the technology among the employees before the implementation of ODT into the strategy and the alignment of the business models can occur (Mukherjee, 2018;Tronvoll et al, 2020;Wu et al, 2021b). This approach contrasts with previous studies, which have called for strategy alignment followed by the search for and implementation of appropriate technologies (Bosman et al, 2020;Sinha and Fukey, 2021). SME employees have indicated that there is a knowledge gap regarding the handling of the collected data.…”
Section: Discussionmentioning
confidence: 97%
“…Incubators assist early-stage teams in identifying the potential to grow a startup business. The process of defining the problem and validating solution assumptions is based on customer needs and is achieved using customer discovery; this involves collecting interview data from potential customers and interpreting the data through thematic analysis [15]. The process increases the likelihood that a startup business will create a solution of value that customers are willing to purchase.…”
Section: Background Higher Education Opportunities In Engineering Des...mentioning
confidence: 99%